Avaliação qualiquantitativa do modelo de gestão do saneamento básico no nordeste - Ferreira, Bárbara Gomes (2025)
The present investigation evaluated water and sewage services in the states of Northeast Brazil, structuring the analysis into three in-depth analytical studies. The first study, based on data from the National Sanitation Information System (SNIS), examined the technical efficiency and productivity changes in basic sanitation services, considering the periods 2005-2006 and 2016- 2017. Using Data Envelopment Analysis (DEA) and the Malmquist Index, a slight increase in the efficiency frontier of municipalities was observed; however, the average efficiency scores experienced a significant reduction. This decline in total factor productivity was mainly attributed to decreased technical efficiency and technological regression, highlighting critical challenges in water resources management. The second study analyzed the determinants of the operational performance of water and sewage services in the Northeast for the same periods, employing factor analysis to discern the factors shaping the Operational Performance Index (IDO) and quantile regression to elucidate the distributive effects of these determinants. It was revealed that the average tariff, distribution losses index, and water consumption were the variables with the highest explanatory power for advances in operational performance, whereas the number of employees and the urban sewage service coverage showed limited influence, indicating the need for strategic revisions in human resources management and technological infrastructure policies within the sector. The third study integrated additional data from SNIS, the Federation of Industries of the State of Rio de Janeiro (FIRJAN), and the Brazilian Institute of Geography and Statistics (IBGE) to explore the impact of socioeconomic characteristics in the administrative mesoregions of Ceará on the operational performance of municipal water and sewage services, using quantile regression methods and cluster analysis to group municipalities by performance level. The results indicated that improvements in the Human Development Index (HDI) and health conditions are generally correlated with higher performance in municipalities with high operational efficiency, while inequality and education indicators tend to improve performance in municipalities with intermediate levels of operation. Furthermore, it was confirmed that national sanitation policy interventions yielded positive outcomes, especially in municipalities with lower operational performance.